The IMPROVE guidelines (Ischaemia Models: Procedural Refinements Of in Vivo Experiments) - Percie du Sert, Nathalie; Alfieri, Alessio; Allan, Stuart M.; Carswell, Hilary V.O.; Deuchar, Graeme A.; Farr, Tracy D.; Flecknell, Paul; Gallagher, Lindsay; Gibson, Claire L.; Haley, Michael J.; Macleod, Malcolm R.; McColl, Barry W.; et al. (Nature Publishing Group, 2017)
Most in vivo models of ischaemic stroke target the middle cerebral artery and a spectrum of stroke severities, from mild to substantial, can be achieved. This review describes opportunities to improve the in vivo modelling of ischaemic stroke and animal welfare. It provides a number of recommendations to minimise the level of severity in the most common rodent models of middle cerebral artery occlusion, while sustaining or improving the scientific outcomes. The recommendations cover basic requirements pre-surgery, selecting the most appropriate anaesthetic and analgesic regimen, as well as intraoperative and post-operative care. The aim is to provide support for researchers and animal care staff to refine their procedures and practices, and implement small incremental changes to improve the welfare of the animals used and to answer the scientific question under investigation. All recommendations are recapitulated in a summary poster (see supplementary information).